Sotrastaurin in Calcineurin Inhibitor–Free Regimen Using Everolimus in De Novo Kidney Transplant Recipients. Issue 7 (9th May 2013) - Tedesco‐Silva, H.; Kho, M. M. L.; Hartmann, A.; Vitko, S.; Russ, G.; Rostaing, L.; Budde, K.; Campistol, J. M.; Eris, J.; Krishnan, I.; Gopalakrishnan, U.; Klupp, J.
Abstract Sotrastaurin, a novel selective protein‐kinase‐C inhibitor, inhibits early T cell activation via a calcineurin‐independent pathway. Efficacy and safety of sotrastaurin in a calcineurin inhibitor—free regimen were evaluated in this two‐stage Phase II study of de novo kidney transplant recipients. Stage 1 randomized 131 patients (2:1) to sotrastaurin 300 mg or cyclosporine A (CsA). Stage 2 randomized 180 patients (1:1:1) to sotrastaurin 300 or 200 mg or CsA. All patients received basiliximab, everolimus (EVR) and prednisone. Primary endpoint was composite efficacy failure rate of treated biopsy‐proven acute rejection, graft loss, death or lost to follow‐up. Main safety assessment was estimated glomerular filtration rate (eGFR) by MDRD‐4 at Month 12. Composite efficacy failure rates at 12 months were higher in sotrastaurin arms (Stage 1: 16.5% and 10.9% for sotrastaurin 300 mg and CsA; Stage 2: 27.2%, 34.5% and 19.4% for sotrastaurin 200 mg, 300 mg and CsA). eGFR was significantly better in sotrastaurin groups versus CsA at most time points, except at 12 months. Gastrointestinal and cardiac adverse events were more frequent with sotrastaurin. Higher treatment discontinuation, deaths and graft losses occurred with sotrastaurin 300 mg. Sotrastaurin combined with EVR showed higher efficacy failure rates and some improvement in renal allograft function compared to a CsA‐based therapy.